Innovataive Enterprice Development on the Basis of Process, Social and Competent Corporate Governance (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article deals with approaches to the definition of the essence of corporate governance, both domestic and foreign scholars. The essence, advantages and features of application of process and socially competentcorporate management are formulated. The urgency of their implementation for the purpose of providing innovative development of domestic enterprises is investigated.
Keywords: innovative development of enterprise, enterprise governance, corporate governance, process governance, social competent governance.